Ethics and terrorism - Taylor, Max; Horgan, John (Routledge, 2022)
"This book provides a unique insight into the ethical issues and dilemmas facing practitioners and researchers of terrorism and counterterrorism. Ethics play a central if, largely, unrecognised role in most, if not all, issues relevant to terrorism and political violence. These are often most noticeable regarding counterterrorism controversies, while often virtually absent from discussions about academic research practice. At a minimum, ethical issues as they relate to terrorism have rarely been explicitly addressed in a direct or comprehensive manner. The chapters in this edited volume draws on the experience of both practitioners and researchers to explore how a regard to ethical issues might influence and determine research and practice in counter terrorism, and in our understanding of terrorism. Ethics and Terrorism recognizes that there are conflicting and often irreconcilable perspectives from which to view terrorism and terrorism research. In calling for greater attention to these issues, the goal is not to resolve problems, but to explore and clarify the assumptions and dilemmas that underpin our understanding of the personal, institutional and societal ethical boundaries and constraints around terrorism and responses to it. This book will be of value to practitioners and researchers, and to policy makers and the broader interested community. The chapters in this book were originally published as a special issue of the journal Terrorism and Political Violence."--Publisher